Radiation treatment of bladder squamous cell carcinoma in a patient with spina bifida: A case report - D’Souza, Neil (Canadian Medical Association, 2012)
Bladder cancer is the sixth most common cancer in Canada. While most patients present with transitional cell carcinoma, few present with squamous cell carcinoma (SCC). Risk factors for SCC include a history of chronic urinary tract infection, urothelial inflammation and indwelling catheters. We present the management of a patient with locally advanced SCC of the bladder.